Accountability and Transparency in Inland Revenue Services of Lagos and Ogun State, Nigeria - Olugbusi, Omobolanle Mosunmola; Ojo, Olawale (NIU Journal of Humanities, 2021)
Accountability and transparency has always been a major cause for concern for many years as a result of misstatement of the financial statement, fraud and corruption in the public service. Accountability has therefore become imperative, because the keys to wealth creation and the maintenance of a free society have been recognized to be primarily accountability and transparency. The main objective of the study was to examine critically the twin concepts of Accountability and Transparency in internal revenue services of both Lagos and Ogun State the target population comprised of five thousand five hundred (5500) employees from different departments at the headquarters of the study organization. A sample size of three hundred and twenty-nine (329) was drawn from the overall target population. In conclusion, the study showed that, there is significant effect of accountability and transparency on Lagos and Ogun State Internal Revenue Service in the same vein, the questionnaire that was administered it was revealed that political interference contributed to lack of full autonomy and has hindered accountability and transparency in internal revenue service. It is therefore recommended that; government should create an anti-corruption department in the public sector, and it should be saddled with the responsibility of ensuring proper accountability and transparency in Internal Revenue Service’s activities Keywords: Accountability, Transparency, Fraud, Public Service, Inland Revenue.